PEMANFAATAN MEDIA SOSIAL INSTAGRAM DALAM MEMPROMOSIKAN BATIK TRIE - Stefanus, Yordan Ponco; Utama, Louis; Verawati (Jurnal Serina Abdimas, 2023)
Batik is a part of the archipelago's original cultural works which is admired by audiences from all over the world and has a unique history. However, over time, batik is often identified with formal clothing that is old-fashioned, stiff, and only worn by parents in Indonesia by the current millennial generation. The rapid development of internet technology has given rise to social media which today, almost everyone uses as a medium for communicating, obtaining information, socializing and doing business, looking for entertainment and others. Social media creates changes in the way the world works, including the field of marketing, especially promotion and advertising, which results in the creation of online business trends. In order to reach consumers, observations, documentation, and literature studies are carried out to find out the most appropriate promotion concept according to marketing communication theory. Promotional activities carried out using Instagram have proven to be effective in attracting customers. The use of social media is expected to be able to market the products widely so that TRIE's business performance will increase. Batik merupakan salah satu bagian dari karya budaya asli Nusantara yang dikagumi oleh khalayak dari berbagai penjuru dunia dan memiliki sejarah yang unik. Akan tetapi seiring berjalannya waktu, batik kerap kali diidentikkan dengan busana formal yang kuno, kaku, dan hanya dikenakan orang tua di Indonesia oleh generasi milenial pada saat ini. Perkembangan teknologi internet yang semakin pesat kian hari telah melahirkan media sosial yang saat ini, hampir semua orang menggunakannya sebagai media sebagai sarana dalam berkomunikasi, memperoleh informasi, bersosialisasi dan berbisnis, mencari hiburan dan lainnya. Media sosial menciptakan perubahan pada cara dunia bekerja, tak terkecuali bidang pemasaran khususnya promosi dan periklanan yang mengakibatkan terciptanya tren bisnis online. Guna menjangkau konsumen, dilakukan observasi, dokumentasi, dan studi kepustakaan untuk mengetahui konsep promosi yang paling tepat sesuai teori komunikasi pemasaran. Kegiatan promosi yang dilakukan dengan menggunakan media sosial Instagram terbukti efektif menarik pelanggan. Penggunaan media sosial diharapkan dapat memasarkan produk secara luas sehingga kinerja bisnis TRIE semakin meningkat.